Friction between runner and ice - Braghin, F.; Belloni, E.; Melzi, S.; Sabbioni, E.; Cheli, F. (The engineering approach to winter sports, 2016)
The scientific literature on ice friction has a long history, going back to and beyond. It involves many areas of science and engineering, including physics, chemistry, tribology, fluid dynamics, thermodynamics. In this chapter we will focus on only those research that were focused on the interaction of skate and runners with ice. The low ice friction coefficient in competitive sliding sports is the result of a liquid water lubricating layer separating the blade and ice. Two different mechanisms contribute to this liquid layer: frictional heating and pressure melting. The thickness of the meltwater layer varies with ice temperature and sliding speed and is of the order of 1 micro m. Conduction of heat into the ice and slider and lateral squeeze flow of the lubricating liquid from under the slider tend to reduce the thickness of the lubricating layer and hence increase the friction coefficient. Friction is due to the energy dissipated at the contact, i.e. to the ploughing of ice (ice permanent deformation, crushing and extrusion), and to the shear stress in the liquid layer. To be able to predict the sled dynamics as well as to optimize its layout in order to maximize performances, both aerodynamic and ice-runner contact forces have to be accurately predicted. While assessing aerodynamic forces is reasonably well defined (e.g. through wind tunnel tests), ice-runner friction forces are much more difficult to predict and measure since they depend on various parameters, such as ice surface temperature, pressure, humidity, runner material, knife design, etc.